Audience perception of digitized broadcast operation in South west, Nigeria (2015)
This study examines the platform in which the broadcasting stations in South West operate, and the degree to which their transmission influence their audience. The study adopts the survey research design with the use of questionnaire and a qualitative method in the use of interview guide to elicit the needed information. 200 sample size were selected from viewers and listeners of Ondo State Radiovision Corporation, Akure and Splash FM, Ibadan, Oyo State for the study. A total of 182 copies of a questionnaire duly completed were analyzed. The finding of the study reveals that majority of the respondents felt that the technical quality (56.7%), news casting (61.5%), programmes (67%) and audio-visual (72.9%) quality of broadcast station in South-West, Nigeria is poor and the effort put in place by stations and government to transit the country into digital broadcasting is not proactive. The study also reveals that majority of broadcast stations in the South-West, Nigeria are still operating in analogue transmission. Findings also reveal that funding and manpower are the major challenges that are slowing down the smooth switchover from analogue to digital broadcasting. Funds to purchase digital equipment are too costly for stations to source for while funds to train manpower to sustain the equipment are not accessible. This shows that broadcast stations in South-West, Nigeria are still operating in analogue, with poor technical quality and facing challenges of manpower and funding. Hence, the National Broadcasting Commission as a regulatory body should liaise with the federal government for funding support from financial institutions for broadcast stations to fulfill their mandate of digitization.